Rabithah as an Instrument for Attaining Khushu in Salat: The Perspective of KH. Muhammad Utsman Al-Ishaqi - Muhtar, Muhammad Zakki (Lembaga Pengembangan Pesantren dan Diniyah Provinsi Jawa Timur, 2024)
Among the forms of etiquette in prayer is khushu, which involves bringing one's heart into communication with the Creator through prayer. In practice, achieving khushu is not easy. Scholars have their methods to attain khushu in worship. In this regard, Sufi scholars have their instruments for achieving khushu by invoking the spirituality of their teacher as a means to connect with Allah SWT. This method is commonly known as rabithah. This paper explores the argument's validity for rabithah as an instrument for achieving khushu, widely practiced by Sufi adherents of the Naqshabandiyah tariqah. This paper focuses on KH Muhammad Utsman Al-Ishaqi's opinion of rabithah in detail. This qualitative research utilizes library research, with data from literature reviews presented descriptively. Inductive analysis is used to examine Kiai Utsman's works. The results show that Kiai Utsman reintroduces rabithah to achieve khushu in prayer. He reinstates rabithah, which had been considered to deviate from Islamic law.